Improving Mathematical Critical Thinking Skills through Problem-Based Learning in Correlation Analysis for High School Students - Saepulrohman, Ipung; Maryati, Iyam (Department of Mathematics Education Program IPI Garut, 2025)
Penelitian ini termasuk dalam jenis Penelitian Tindakan Kelas (PTK) dengan tujuan untuk mengembangkan kemampuan berpikir kritis matematis siswa melalui penerapan model pembelajaran Problem Based Learning (PBL) pada pokok bahasan Analisis Korelasi. Subjek penelitian yaitu 36 siswa kelas XI SMAN 16 Garut semester genap tahun pelajaran 2024/2025. Studi dilaksanakan selama dua siklus meliputi tahap perencanaan, pelaksanaan, observasi, dan refleksi. Pengumpulan data melalui tes serta non tes. Teknik analisis data dilakukan secara deskriptif kuantitatif dan kualitatif. Hasilnya menunjukkan bahwa skor rata-rata kemampuan berpikir kritis meningkat dari 69,4% pada siklus I menjadi 80,5% pada siklus II. Temuan ini menunjukkan bahwa model PBL efektif dalam meningkatkan kemampuan berpikir kritis matematis siswa sehingga layak menjadi alternatif strategi pembelajaran aplikatif di kelas. This study is classified as Classroom Action Research (CAR) aimed at developing students' mathematical critical thinking skills through the implementation of the Problem-Based Learning (PBL) model on the topic of Correlation Analysis. The research subjects consisted of 36 eleventh-grade students from SMAN 16 Garut during the second semester of the 2024/2025 academic year. The study was conducted over two cycles, encompassing the stages of planning, implementation, observation, and reflection. Data were collected using both test and non-test instruments. The data analysis was carried out using both quantitative and qualitative descriptive techniques. The results revealed that the average score of students’ critical thinking skills increased from 69.4% in the first cycle to 80.5% in the second cycle. These findings suggest that the PBL model is effective in enhancing students’ mathematical critical thinking skills and is therefore suitable for use as an alternative instructional strategy in the classroom.